Dampak Perubahan Sosial Budaya Terhadap Pendidikan - Wisman, Yossita; Bernisa, Bernisa; Dony, Garry William; Sontoe, Sontoe (FKIP Universitas Palangka Raya, 2025)
Social and cultural change is a phenomenon that occurs continuously in every society. These changes encompass shifts in social structures and cultural patterns influenced by various internal and external factors. Education, as an integral part of society, is also affected by these dynamics, influencing curriculum design, teaching methodologies, and educational management. Rapid and revolutionary changes demand an adaptive educational system that remains relevant to contemporary needs. Therefore, understanding the relationship between socio-cultural changes and education is crucial in designing educational policies that are more responsive and adaptive to social dynamics.